Safety, effectiveness and hesitancy of COVID-19 vaccination in children: A cross-sectional study in Pakistan - Zaufishan, Zaufishan; Usman, Muhammad; Fishan Mumtaz, Khandah; Bilal, Rabiea; Arshad, Alina; Khan, Humaira Majeed (Frontiers in Public Health, 2023)
Background The elevated risk of serious complications like myocarditis and pericarditis after COVID-19 vaccination, especially in adolescent has been reported in some instances that need to be tested in regional populations and different ethnicity groups. The purpose of the study was to evaluate the side effects, hesitancy, and effectiveness outcomes following COVID-19 vaccination among children in Pakistan. Methods The study was planned using a cross-sectional design and data from Children and Adolescents (CA) was collected through a convenient sampling method using a validated questionnaire between February to July 2022. A total of 1,108 CA between the age of 12–18 years who received one or two doses of vaccine were selected and data were collected through direct interviews with respondents. Results The results showed that among 99.8% of respondents who received the Pfizer COVID-19 vaccine, 72.3% of respondents were partially vaccinated (with one dose) while 27.7% were fully vaccinated (with two doses). COVID vaccination regime had a favorable safety profile in children as compared to adults. Vaccine hesitancy in children was reported to be 52.4% and the most common reasons for hesitance were the assumption that the vaccine is not safe (23.7%), the vaccine is not required (19.6%) and the vaccine is not effective (10.4%). The reported side effects were mainly mild (88.5%) followed by moderate (10.6%) and only 0.8% were of severe intensity. Post-vaccination local side effects of mild intensity were common with an onset of an average of 24 h (68%) and a duration of 2–3 days (60.6%). The reported side effects were significantly associated with gender (p = 0.00) while age had no significant effect on the occurrence of side effects. Overall, the vaccine was well tolerated by children and adolescents and was effective in preventing the reoccurrence of COVID-19 infection in 99.9% of participants. Conclusion COVID-19 vaccine by Pfizer approved by the FDA for use in CA 12–18 years of age was well tolerated with a good safety profile and no serious adverse drug reactions were reported. The vaccine side effects were mild (88.5%) and lasted for an average of 2–3 days only (60.4%). The vaccine was effective in safeguarding Children against COVID-19 infection.